Antifungal Activity of 10 Guadeloupean Plants. (27th December 2012) - Biabiany, Murielle; Roumy, Vincent; Hennebelle, Thierry; François, Nadine; Sendid, Boualem; Pottier, Muriel; Aliouat, El Moukhtar; Rouaud, Isabelle; Lohézic‐Le Dévéhat, Françoise; Joseph, Henry; Bourgeois, Paul; Sahpaz, Sevser; et al.
<x xml:space="preserve">Abstract</x> Screening of the antifungal activities of ten Guadeloupean plants was undertaken to find new extracts and formulations against superficial mycoses such as onychomycosis, athlete's foot, Pityriasis versicolor, as well as the deep fungal infection Pneumocystis pneumonia. For the first time, the CMI of these plant extracts [cyclohexane, ethanol and ethanol/water (1:1, v/v)] was determined against five dermatophytes, five Candida species, Scytalidium dimidiatum, a Malassezia sp. strain and Pneumocystis carinii. Cytotoxicity tests of the most active extracts were also performed on an HaCat keratinocyte cell line. Results suggest that the extracts of Bursera simaruba, Cedrela odorata, Enterolobium cyclocarpum and Pluchea carolinensis have interesting activities and could be good candidates for developing antifungal formulations. Copyright © 2012 John Wiley & Sons, Ltd.